Comparative analysis on immunity of volleyball players before and after taking grape procyanidins sports supplement - Tang, X.; Guo, M. (Revista Brasileira de Medicina do Esporte, 2021)
Grape proanthocyanidin is a good health product, without side effects and excellent biological activity, but research in the field of sports tonic is still relatively slow. Currently, the technology of preparation and extraction of grape proanthocyanidins is relatively mature. This fact laid the groundwork for sports tonic proanthocyanidin research. This study first described the biological structure of proanthocyanidin in grapes, and built the immune system of volleyball players before and after taking proanthocyanidin sports supplements. He then analyzed the factors that influence immunity. The results show that the primary index subsystem is consistent with the total system in each phase, but there are still few differences over time, which can be divided into four phases: development, recession, recovery and stability; at the level of scientific training it is reasonable. Male and female athletes take exercise supplements containing proanthocyanidin at each level of training. Regarding humoral immunity and cellular immunity, there was no adverse reaction. This study may offer some reference value for other athletes before and after taking proanthocyanidin as a sports supplement.